In Vitro Analysis of the Proliferation of HaCaT Cells Stimulated by Pigments Used for Maxillofacial Prostheses - Marcelo Coelho Goiato; Adhara Smith Nobrega; Estefania Marrega Malavazi; Aline Satie Takamiya; Sandra Helena Penha de Oliveira (Wolters Kluwer Medknow Publications, 2019)
Introduction: Although physical and mechanical properties are extremely important for the effectiveness of prosthetic treatment, materials used for facial rehabilitation should be biocompatible, as the maxillofacial prosthesis is in close contact with the patient's skin. The objective of this study was to evaluate the influence of different eluates formation periods obtained from the methyl tetrazolium salt (MTT) and Alamar Blue assays, analyzed in different silicones and pigments used in the manufacture of maxillofacial prostheses in the proliferation of human keratinocytes (HaCaT cells). Materials and Methods: For the preparation of samples, A2 A-2186 and Silastic MDX4-4210 silicones and three types of pigments (bronze, black, and medium pink) were selected. Two of the pigments were specific for the characterization of the prosthesis and already available in dental market in bronze and black colors, and a new pigment was tested in the medium pink color. Five samples were prepared for each group and distributed according to the type of silicone and pigment added, aiming to prepare the eluates after 24 and 72 h of sample's immersion in culture medium. In vitro assays of MTT and Alamar Blue were performed for cytotoxic analysis. Data obtained were submitted to analysis of variance and the Tukey test, with a 5% significance level. Results: All groups had cell proliferation percentages higher than 75%, indicating absence of cytotoxicity. Conclusions: It can be concluded that all the materials used are not cytotoxic, including the proposed new pigment, for the preparation of maxillofacial prostheses.